Effect of Rigidity of Plinth Beam on Soil Interaction of Modeled Building Frame Supported on Pile Groups - Ravi Kumar Reddy, C.; Gunneswara Rao, T.D. (Civil Engineering Dimension, 2014)
This paper presents the effect of rigidity of plinth beam on a model building frame supported by pile groups embedded in cohesionless soil (sand) through the results of static vertical load tests. The effect of rigidity of plinth beam on displacements and rotation at the column base and also shears and bending moments in the building frame were investigated. In the analytical model, soil nonlinearity in the axial direction is characterized by nonlinear vertical springs along the length of the pile (t-z curves) and at the tip of the pile (Q-z curves) while in the lateral direction by the p-y curves. Results revealed that, shear force and bending moment values which were back calculated from the experimental results, showed considerable reduction with the reduction of the rigidity of the plinth beam. The response of the frame from the experimental results is in good agreement with that obtained by the nonlinear finite element analysis.